Construction claims in the fast track mega infrastructure projects of Saudi Arabian Construction Industry - Shaikh, Haseeb Halim (2021)
The construction industry has rapidly grown in Saudi Arabia and there are many upcoming projects to be finished in a limited time to meet the Saudi Vision 2030. Due to the shortage of time, most of the projects are managed by fast track system. It has been observed that the number and amount of construction claims are increasing in Saudi Arabian construction industry. The existing studies lacks in claims management especially on fast track projects in Saudi Arabia due to governance system. Therefore, this research aims to control the possible claims and provide suggestions to improve the project performance by better claim management approach in Saudi Arabian construction industry. Hence, this study investigates and evaluates the major types and causes of claims that occur especially in the fast track mega infrastructure projects of Saudi Arabia. It also provides remedial measures to deal with claims of such projects. Detailed literature has been carried out to identify the types and causes of claims affecting the fast track projects followed by questionnaires survey. The data was collected from the Riyadh Metro project and was analyzed by Average Mean Index (AMI) method using SPSS and Analytical Hierarchy Process (AHP) using Expert Choice. The remedial measures were suggested based on targeted experts’ opinion. This research concluded that major causes of claims on fast track mega projects were unclear scope of work, incomplete contract documents, design change by the client and unforeseen underground utilities. This study suggested that the claim management process should be implemented in construction projects while dealing with claims, especially in the fast track mega infrastructure projects of the Saudi Arabian construction industry. Early identification of claims helps the stakeholders to resolve the issues immediately. The findings of this research will be assisting the construction professionals and Saudi government to deal with the upcoming fast track mega projects such as Makkah Metro, Jeddah Metro and Dammam Metro projects.